2021
DOI: 10.1371/journal.pone.0245408
|View full text |Cite
|
Sign up to set email alerts
|

Association of IRS1 (Gly972Arg) and IRS2 (Gly1057Asp) genes polymorphisms with OSA and NAFLD in Asian Indians

Abstract: Aim and objective The aim of the study was to investigate the relationships between insulin receptor substrate (IRS) 1 (Gly972Arg) and IRS2 (Gly1057Asp) genes with obstructive sleep apnea (OSA) and non-alcoholic fatty liver disease (NAFLD) in Asian Indians. Method A total of 410 overweight/obese subjects (130 with OSA with NAFLD, 100 with OSA without NAFLD, 95 without OSA and with NAFLD and 85 without OSA and without NAFLD) were recruited. Degree of NAFLD was based on liver ultrasound and of OSA on overnight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Studies have shown that the frequency of the Arg allele of the Gly972Arg polymorphism of IRS-1 gene was significantly increased in NAFLD. Gly972Arg carriers are at significantly higher risk of NAFLD ( Bhatt and Guleria, 2021 ). The association between IRS-1 gene polymorphism and incident type 2 diabetes has been demonstrated in both the Asian and Caucasian populations ( Dongiovanni et al, 2010 ; Li et al, 2016 ).…”
Section: Nafld and Coronary Artery Diseasementioning
confidence: 99%
“…Studies have shown that the frequency of the Arg allele of the Gly972Arg polymorphism of IRS-1 gene was significantly increased in NAFLD. Gly972Arg carriers are at significantly higher risk of NAFLD ( Bhatt and Guleria, 2021 ). The association between IRS-1 gene polymorphism and incident type 2 diabetes has been demonstrated in both the Asian and Caucasian populations ( Dongiovanni et al, 2010 ; Li et al, 2016 ).…”
Section: Nafld and Coronary Artery Diseasementioning
confidence: 99%
“…Thereby, malfunction of the IRS impairs insulin signaling and increases the risk of insulin resistance. The loss-of-function rs1801278 Gly927Arg polymorphism diminishes the IRS-1 activity and inhibits the insulin receptor autophosphorylation, causing a reduction in insulin signaling [ 86 ]. A recent Pakistani population study demonstrated a correlation between the Gly972Arg variant of IRS-1 and insulin resistance in T2DM [ 87 ].…”
Section: Metabolic-related Genes Influencing Nafldmentioning
confidence: 99%
“…The Gly1057Asp variation of the IRS2 gene has been widely documented, and it is thought to be linked to insulin resistance, T2D, and obesity. Gly1057Asp inside IRS2 has been linked to greater insulin resistance and T2D in obese Caucasian youngsters, Kurdish ethnics, Iranians, and Asian Indians [66,[76][77][78], while research in a Turkish women's population suggests that this genetic variation may be linked to GDM as well [79]. However, the genetic variant of IRS2 Gly1057Asp was significantly associated with risk of T2D only in female Bangladeshi population, not males, and the authors were unable to replicate the association of IRS2 Gly1057Asp with obesity [80], while no association with obesity has been found in obese Polish pregnant women [81], implying more appropriate controls for related confounding factors, and a larger sample size is required to confirm this finding.…”
Section: Gene Polymorphism Of Irssmentioning
confidence: 99%